MoS2/TiO2 Edge‐On Heterostructure for Efficient Photocatalytic Hydrogen Evolution. Issue 14 (6th May 2016) - He, Haiyong; Lin, Junhao; Fu, Wei; Wang, Xingli; Wang, Hong; Zeng, Qingsheng; Gu, Quan; Li, Yongmei; Yan, Cheng; Tay, Beng Kang; Xue, Can; Hu, Xiao; et al.
Abstract : Via edge engineering, a facile two‐step method is demonstrated that produces solid edge‐on junctions between TiO2 and few‐layered MoS2 in large scale. MoS2 /TiO2 edge‐on heterostructures result in high conductive MoS2 /TiO2 interfaces and optimized electron transport pathways that facilitate the electron–hole pair separation, leading to an efficient solar water splitting.